The impact of education on happiness : evidence from a natural experiment - Ventura, Gabriel Vieira (2021)
This dissertation aims to examine the causal effect of education on happiness and satisfaction with several life domains using data from the Turkish Life Satisfaction Survey. To tackle possible endogeneity of education, we implement the method of instrumental variables (IV) and make use of the 1997 education reform, which prolonged compulsory schooling from 5 to 8 years in Turkey, as a source of exogeneous variation in education. The IV estimates indicate that education has no statistically significant effect on happiness for both genders. Moreover, the impact of education on various life satisfaction domains differs between men and women. The IV results provide evidence that for females, having at least a middle school degree increases the likelihood of being satisfied with household income, health, and housing quality. Among males, we find that education has a negative and statistically significant effect on job satisfaction.